2022
DOI: 10.31020/mutftd.960984
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nomophobic Behavior of Student Nurses Using Smartphones on Social Phobia

Abstract: Aim: This study was carried out to determine the effects of the nomophobic behaviors of student nurses using smartphones on their social phobia levels. Methods: This cross-sectional and correlational study was carried out between 1 March and 30 September 2019 with the participation of nursing students (N=409) enrolled at a state university in Turkey. Results: A significant relationship was determined between nomophobic behavior and social phobia according to the results of the regression and correlation analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Studies mostly examined its effect on students with high-level smartphone dependency. Upon the review of studies evaluating the effect of nomophobia on nursing students, it was discerned that the study by Okuyan et al asserted that nursing students were moderately nomophobic (26) whilst the study by Özdemir et al stated that nursing students were highly nomophobic (27). Besides, in the study performed by Aguilera-Manrique to analyze the relationship between nursing students' nomophobia levels and their distractibility in clinical practices in association with smartphone use, it was identified that nursing students were moderately nomophobic (28).…”
Section: Discussionmentioning
confidence: 99%
“…Studies mostly examined its effect on students with high-level smartphone dependency. Upon the review of studies evaluating the effect of nomophobia on nursing students, it was discerned that the study by Okuyan et al asserted that nursing students were moderately nomophobic (26) whilst the study by Özdemir et al stated that nursing students were highly nomophobic (27). Besides, in the study performed by Aguilera-Manrique to analyze the relationship between nursing students' nomophobia levels and their distractibility in clinical practices in association with smartphone use, it was identified that nursing students were moderately nomophobic (28).…”
Section: Discussionmentioning
confidence: 99%